Hasil Belajar Siswa Ditinjau Dari Keaktifan Bertanya Pada Materi Struktur Tumbuhan Siswa Kelas VIII Smp Negeri 2 Sawit Boyolali Tahun Ajaran 2015/2016 - Khomariyah, Siti Ayu; , Dr. Sofyan Anif, M.Si (2016)
The learning outcome is the evidence of success that has been achieved or obtained by students in learning due to their efforts and thoughts which is stated in the form of basic knowledge and skills contained in various aspects of life so that it appears to the individuals' behavioral changes quantitatively.This research aims to find out : the influence of activeness in questioning for studentstowards the learning outcome within the topic discussed "Plant's Structure" in SMP Negeri 2 SawitBoyolali Year 2015/2016.This research is quantitative research, especially explanative research type. The data is analyzed using parametric test One-Way ANOVA by using SPSS version 20.0 program. The population of the research is students of eighth grade in SMP Negeri 2 SawitBoyolali Year 2015/2016.The research sample consists of three classes. The technique of taking sample uses Simple Random Sampling. Data collection method has been done by observation and documentation. Data analysis technique with an extent of significance 5% obtained that: (1) the value of sig. 0,000<0,05, therefore the learning outcome of the topic discussed "plant's structure" is influenced by students' activeness in questioning in SMP Negeri 2 Sawit Boyolali Year 2015/2016. (2) the value of sig. 0,001<0,05, therefore the learning outcome of the topic discussed "plant's structure" is influenced by students' activeness in questioning in SMP Negeri 2 Sawit Boyolali Year 2015/2016. Thus it can be concluded that students' learning outcomes within the topic discussed "plant's structure" for students grade eight are influenced by activeness in questioning in SMP Negeri 2 Sawit Boyolali year 2015/2016.